Croatia : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This Selected Issues paper and Statistical Appendix deals with the data interpretation problems in the Croatian balance of payments and discusses in detail the overestimation of the size of the external current account deficit in the official statistics. It examines the behavior of the monetary aggregates in Croatia using econometric methods. The structure and performance of the banking sector is also analyzed, including the effects of competition and ownership structure on profitability and interest rate spreads.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet